2015
DOI: 10.1002/pc.23402
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, microstructure, mechanical, and thermal properties of in situ polymerized polyimide/organically modified sericite mica composites

Abstract: In this work, sericite mica was initially modified with a multi-step procedure and the novel composites of polyimide (PI) with the organophilic sericite mica were subsequently synthesized via in situ polymerization technique. XRD patterns revealed d 002 -spacing of clay was expanded from 0.99 to 2.77 nm. TEM photographs indicated majority of the organoclay exhibited an exfoliated morphology structure in composites with 5 wt% filler loading. Several critical properties of composites such as thermal stability, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The absorption bands at ~ 472 cm -1 and 800 cm -1 are assigned to Al-O and Si-O stretching and bending respectively. The band near 1024 cm -1 is assigned to Si-O-Si stretching (Zhang et al, 2016), the two absorption bands at near 3445 cm -1 and 3622 cm -1 were assigned to -OH stretching vibration of adsorbed water and stretching of lattice OH of sericite mica, respectively. After the original mica was activated at 600 o C, 700 o C and 800 o C, structure did not seem to be affected, but the intensity of absorption band at near 3622 cm -1 decreased gradually with the increase of activation temperature due to dehydroxylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption bands at ~ 472 cm -1 and 800 cm -1 are assigned to Al-O and Si-O stretching and bending respectively. The band near 1024 cm -1 is assigned to Si-O-Si stretching (Zhang et al, 2016), the two absorption bands at near 3445 cm -1 and 3622 cm -1 were assigned to -OH stretching vibration of adsorbed water and stretching of lattice OH of sericite mica, respectively. After the original mica was activated at 600 o C, 700 o C and 800 o C, structure did not seem to be affected, but the intensity of absorption band at near 3622 cm -1 decreased gradually with the increase of activation temperature due to dehydroxylation.…”
Section: Resultsmentioning
confidence: 99%
“…In a typical intercalation process, the sericite mica was firstly activated at high temperatures. Subsequently, a modified sericite mica with interlayer spacing enlarged was obtained by reaction with nitric acid and a series of interlayer cation exchange reactions, which did not affect the surface modification of sericite mica (Li et al, 2011;Zhang et al, 2016). The hydroxyl groups on the surface of sericite mica reacted with a variety of different coupling agents (Bose & Mahanwar, 2010;Ismail et al, 2012;Ismail et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of literatures about the preparation and properties of PI/layered silicate hybrid films have been reported (22), properties of PI/mica hybrid films have not yet received sufficient attention. It refers that the dielectric properties of PI/mica hybrid films have not been fully studied, and no study has been reported on the coefficient of thermal expansion and thermal properties of this kind of hybrid films (23). Furthermore, dispersing inorganic particles evenly in PI matrix is a key factor that affects the properties of hybrid film, and the surface modification of inorganic particles can improve the compatibility between the inorganic phase and the organic phase (24).…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric foams with inorganic reinforcing materials may effectively decrease the volumetric shrinkage, improve the thermal stability, and enhance flame resistance . The common reinforcing materials used for polyimide foams include graphene, graphene oxide, nanoclay, silica, silver nanowires, etc. Vermiculite is one kind of layered water aluminum silicate secondary metamorphic mineral containing magnesium, ore like mica, with low cost, light weight, and heat insulation characters .…”
Section: Introductionmentioning
confidence: 99%